1997
DOI: 10.1016/s0017-9310(96)00309-2
|View full text |Cite
|
Sign up to set email alerts
|

Transition of oscillatory floating half zone convection from Earth's gravity to microgravity

Abstract: Abstract-Oscillatory features of floating half zone convection were experimentally studied by using the drop shaft facility of Japan MicrogravityCenter which supported microgravity period of 10 s. Coordinated measurements including free surface deformation and oscillation, temperature and flow pattern in both lg and micro-g environment were obtained. The oscillatory frequency and amplitude in micro-g condition were lower and larger than the ones in l-g condition, respectively. The results gave, at first time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, the gap may be disappeared and two curves connect to form a cusp if the geometrical aspect A is small. The microgravity experiments were performed with the drop shaft facility by Yao et al [6] and Sakurai and Hirata [7]. Recently, similar conclusion was obtained by the linear instability analysis for the case of the microgravity environment, but the in¯uence of liquid bridge volume on the onset of oscillation is quite dierent in cases of smaller Prandtl number [8] in comparison with the cases of large Prandtl numbers [9].…”
Section: Introductionmentioning
confidence: 59%
“…However, the gap may be disappeared and two curves connect to form a cusp if the geometrical aspect A is small. The microgravity experiments were performed with the drop shaft facility by Yao et al [6] and Sakurai and Hirata [7]. Recently, similar conclusion was obtained by the linear instability analysis for the case of the microgravity environment, but the in¯uence of liquid bridge volume on the onset of oscillation is quite dierent in cases of smaller Prandtl number [8] in comparison with the cases of large Prandtl numbers [9].…”
Section: Introductionmentioning
confidence: 59%
“…The authors speculated that the stabilizing buoyancy gradient present in the ground experiments could be partially responsible. Yao et al (1997) used a 10-s drop tower to study changes in temperature and free-surface oscillations in half zones of 10 cS silicone oil (Pr = 105). The zones had 3 and 4 mm diameters with aspect ratios of A = 1.6.…”
Section: Microgravity Experimentsmentioning
confidence: 99%
“…The experiments of Yao et al (1997) and Han et al (1996) reported on above included considerations of the volume of liquid occupying the liquid bridge. Other sets of experiments by Hu and colleagues (Cao et al 1992;Shu et al 1994) have also examined the influence of free-surface deformation as quantified by either a diameter ratio or volume ratio.…”
Section: Free-surface Deformationmentioning
confidence: 99%
“…The transition process from 1g to mg for the usual model of a floating half zone with typical scales of 3 and 4 mm diameter has been discussed in Ref. [13]. The present study gives the results for a different typical scale (5 mm diameter) and experimental medium.…”
Section: Methodsmentioning
confidence: 74%
“…The authors [11,12], Yao et al [13] and Schwabe [14] have compared oscillatory features between normal gravity (1g) and mg conditions. Yao et al [13] examined the transition process from 1g to mg, and while Schwabe et al [14] found that the frequency was almost the same between 1g and mg conditions, the amplitude of temperature oscillation was greater under 1g conditions than under mg. Despite this work, however, the differences in the oscillatory state between 1g and mg are not yet clear.…”
Section: Introductionmentioning
confidence: 99%